Gastrointestinal comorbidities in patients with psoriasis in the Czech Republic: The results of 189 patients with psoriasis and 378 controls - Juzlova, Katerina; Votrubova, Jana; Dzambova, Martina; Gopfertova, Dana; Hercogova, Jana; Smerhovsky, Zdenek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
AIMS: The aim of the study was to investigate gastrointestinal comorbidities, identify risk factors and detect the early stages of autoimmune gastrointestinal diseases, such as Crohn's disease, ulcerative colitis and coeliac disease in patients with psoriasis. METHODS: This was a hospital-based case-control study. Patients with chronic plaque psoriasis were included as cases. The control group consisted of patients with other skin diseases and who complied with the same selection criteria as cases. Two controls were selected per one case. We analysed the following antibodies (ASCA, AEP, p-ANCA, AGC, EMA, ARA, tTG, AGA) and non-specific signs of gastrointestinal diseases. RESULTS: There were significant differences between cases and controls in several parameters. Leucocyte count, CRP, total protein, transglutaminase IgA antibodies and p-ANCA were statistically significant between groups (P < 0.05). In the binary logistic model, leucocyte count and p-ANCA (for all parameters included in the logistic model P ≤ 0.001) were associated with psoriasis. CONCLUSION: Patients with psoriasis should be regularly screened for coeliac and inflammatory bowel disease. Early diagnosis of gastrointestinal diseases and risk factors may prevent complications and greatly improve the patient's quality of life.
Keywords: Transglutaminases; Humans; Case-Control Studies; Colitis, Ulcerative; počet leukocytů; C-reaktivní protein; časná diagnóza; ulcerózní kolitida; Psoriasis; studie případů a kontrol; Quality of Life; inflammatory bowel diseases; Chronic Disease; Female; protilátky proti cytoplazmě neutrofilů; psoriáza; Crohn Disease; lidé; Leukocyte Count; Immunoglobulin A; kvalita života; transglutaminasy; celiakie; ženské pohlaví; Male; psoriasis; chronická nemoc; Antibodies, Antineutrophil Cytoplasmic; Czech Republic; coeliac disease; Crohnova nemoc; Early Diagnosis; Celiac Disease; imunoglobulin A; Česká republika; mužské pohlaví; C-Reactive Protein